Students Difficulties in Mastering Clauses - Haryanti, Sri; Setyandari, Ana (International Journal of Active Learning, 2018)
This study aims to know the students mastery on clauses of the fifth semester students of English Education Study Program, Teacher Training and Education Faculty, Widya Dharma University of Klaten in academic year 2016/2017 and the difficulties faced in comprehending clauses. The method of collecting data is the test. The method of analyzing data is statistics in the form of mean score. The results are the students mastery on clauses of the fifth semester students of English Education Study Program, Teacher Training and Education Faculty, Widya Dharma University of Klaten in academic year 2016/2017 is good; and the difficulties faced in comprehending clauses are identifying the functions of noun clause, determining the introductory conjunction, making adjective clause appropriately, selecting the appropriate verb, and determining the tense.